Starševstvo v reorganiziranih družinah v Sloveniji - Pesjak, Katja (Družboslovne razprave, 2011)
The article focuses on relationships between biological parents and children and step-parents and children in the context of everyday life in reorganised families in Slovenia. The aim was to answer three questions: how are relations between biological parents and children in reorganised families redefined, what are biological parents perceptions of relations between step-parents and children, and what are step-parents perceptions of relations between them and children. Relations between biological parents and children are being transformed in the context of establishing new partnerships. Biological parents form their perceptions of the relationship between step-parents and children and perceptions of the constitutive elements of the relationship through life in a single-parent family and a reorganised family and through parenting experiences in a nuclear family. Step-parents perceptions stem from the determinants of the stepparents' role.
Keywords: Parenthood; Starševstvo; Starši; Parents; child; Children; Otroci; Interpersonal relations; Medosebni odnosi; Slovenia; Slovenija; sociologija družine